Biocatalytic reductive amination with CRISPR-Cas9 engineered yeast - Arne Hagman; Olof Stenström; Göran Carlström; Mikael Akke; Carl Grey; Magnus Carlquist (Scientific Reports)
Abstract Metabolically engineered baker’s yeast can be used to produce chiral amines through whole-cell bioconversion of prochiral ketones. This study investigates the modulation of the alanine-pyruvate metabolic node to enhance reductive amination, using the stereoselective conversion of benzylacetone to (S)-1-methyl-3-phenylpropylamine (MPPA) as a model reaction. Chromosomal integration of multiple copies of the promiscuous omega transaminase from Chromobacterium violaceum (cv-ATA) resulted in an active yeast catalyst. Physiological characterization in bioreactors under aerobic batch cultivation revealed that amine production occurred only under post-diauxic growth on ethanol. To reduce native alanine utilization, the endogenous alanine aminotransferase (ALT1) was knocked out and replaced with cv-ATA. To rapidly employ this strategy in other strains, a simple CRISPR/cas9 method for universal gene replacement was developed. The replacement of ALT1 with cv-ATA improved the reaction by 2.6-fold compared to the control strain with intact ALT1. NMR measurements of metabolites originating from 15N L-alanine and 13C glucose indicated that pyruvate formation during growth on glucose inhibited amine production. Under optimal conditions, the biocatalytic bioconversion of benzylacetone to MPPA reached a yield of 58%.